Die südandine und die südbrasilianische Araukarie. Ein ökologischer Vergleich - Golte, Winfried (ERDKUNDE, 1977)
There are two species Araucaria conifers in South America (Fig.1): A.araucana in the central section of the southern Andes, A. angustifolia in southern Brazil. In view of the great similarity and close systematic relationship of both species on the one hand, and the seeming difference of their climatic conditions on the other hand, the question arises as to the common ecological characteristics of the two areas of occurrence, which are decisive for their flourishing. It appeared that the annual hygric course of both areas was in agreement. A very humid season alternates with another one of irregular precipitation and frequent dry weather, which has prolific radiation. In both the regions the hygric seasons carry on an inverse relationship as regards the thermal seasons in the area in which A. araucana occurs, episodic dryness in summer and in the larger part of the area in which A. angustifolia, episodic dryness in winter. It is demonstrated that both species of Araucaria are adapted to these climatic conditions, not only thanks to their xeromorphic habit, but also as a result of an endogenic rhythm synchronized primarily with the hygric seasons. This endogenic rhythm finds its expression in the growth periodicity (annual growth rings) and the reproductive cycle (seed formation).